Humans and Tits in the City: Quantifying the Effects of Human Presence on Great Tit and Blue Tit Reproductive Trait Variation - Corsini, Michela; Dubiec, Anna; Marrot, Pascal; Szulkin, Marta (Frontiers in Ecology and Evolution, 2017)
Environmental conditions are key drivers of life-history evolution, and the urban environment is an extreme form of land-use readily inhabited by avian wildlife, whose life-history variation in such altered environment is still poorly understood. Recently, the study of environmental variables associated with urban living – which include shifts in temperature, light, noise or food availability – has attracted increased attention. Another environmental axis that sets the urban space at odds relative to natural habitats is high human abundance, yet very little is known about its effect on avian fitness. We developed a protocol to quantify human presence by performing repeated counts of humans on the ground within a 15m radius of nestboxes monitored in two centrally-located study areas of a European capital city. In parallel, a GIS-based approach was used to infer nestbox distance to the nearest path and road. Multiple counts of human presence around each nestbox yielded moderate to high repeatabilities (0.6≤r≤0.8) while requiring considerable resources time- and people- wise. In contrast, GIS-based estimates of nestbox distance to paths and roads were time efficient and generated highly repeatable results. The effects of (i) human presence around each nestbox, (ii) nestbox distance to the nearest path and (iii) nestbox distance to the nearest road were tested on reproductive traits of blue tits Cyanistes caeruleus and great tits Parus major breeding in two urban sites. Human presence did not influence blue tit or great tit life-history traits and reproductive success, suggesting reproductive habituation to humans in an urban landscape. In contrast, nestbox distance to roads shortened incubation time in great tits while nestbox distance to paths increased incubation time in blue tits. Moreover, blue tit offspring two weeks after hatching were lighter closer to roads. Our study confirms the reliability of a field protocol capturing human presence around multiple fixed locations that can be easily implemented in either urban or rural landscapes. At the same time, it appears that when applied to two urban sites where habituation to humans might have occurred, it is infrastructural networks rather than human presence per se that played a greater role in tit reproductive